The potential of the adaptive thermal comfort concept in long-term actively conditioned buildings for improved energy performance and user wellbeing. Issue 3 (November 2020) - Hellwig, Runa T.; Teli, Despoina; Boerstra, Atze
Abstract: Technological progress in conditioning practice combined with prevailing thermal comfort criteria, created stable, tightly controlled indoor temperature bands. Research shows indoor temperatures to be increasing in the heating period, leading to higher building energy use than planned. Field studies provide proof that occupants not in control of their indoor climate are more dissatisfied and report problems in wellbeing. Widening temperature bands could be an effective measure leading to energy conservation, increasing satisfaction and, as shown recently, helping to mitigate health problems related to our way of life. The adaptive approach to thermal comfort postulates that people's thermal comfort perception adapts to the indoor and outdoor climatic conditions they normally experience. However, according to standards, the adaptive model is applicable only to passively conditioned (free-running) buildings, even though the adaptive principles may well apply also to actively conditioned buildings. Our review found studies demonstrating positive health effects and energy conservation potential in permanently or seasonally conditioned buildings. On this basis, the potential of the adaptive approach and translations into concrete design or operation solutions for actively conditioned buildings are discussed in this paper. We conclude that the adaptive concept offers a potential for indoor climate control in actively conditioned buildings in the temperate and cold climates.